Factors associated with the use of herbal medicines for oral problems by patients attending the clinics of the School of Dentistry, Federal University of Juiz de Fora, Brazil - Janice Simpson de Paula; Alexandre Marques de Resende; Fábio Luiz Mialhe (Universidade Estadual de Campinas, 2015)
Aim: To evaluate differences in sociodemographic characteristics (gender, age, educational level and income) between users and nonusers of phytotherapy for dental purposes; the degree of population's knowledge of herbal medicines for dental needs; and whether patients inform the health professional about their use of phytotherapy. Methods: A questionnaire was applied to 100 patients in waiting rooms of the School of Dentistry of the Federal University of Juiz de Fora, in 2008, to inquire about sociodemographic variables and other factors associated with the use of phytotherapy. Statistical analyses were carried out using the chi square statistical test to calculate association between the variables, with 0.05 as level of significance. Results: It was observed that 64.8% of participants were women with a mean age of 43.9±15.1 years. Phytotheraphy use for treatment of oral problems was reported by 37% of patients interviewed in this study. Significant differences were found between users and non-users of herbal medicines for oral problems, associated with the patient's age (p<0.05) and previous experience with use of phytotherapy to treat general health problems (p<0.001). Conclusions: The results emphasize the need for more scientific evidence of the efficacy of herbal medicinal products already incorporated in the popular knowledge to treat oral problems in order to make it an accessible and alternative method for prevention and therapy in dentistry